(untitled) (Research, Society and Development, 2023)
Born in the 1960s, the Internet has become the most important media outlet of recent times, being responsible for the largest number of information spread in the world. Despite the undeniable importance it is necessary to analyze its benefits and also what is obscure in this discovery that transformed the land into a large global village. In this sense, the objective of this study was to investigate the current reality of virtual crimes in Brazil and how they affect victims from the biopsychosocial point of view. This is a descriptive review of the literature, that is the critical, meticulous and broad analysis of publications arising from a particular theme or a certain area of knowledge Through consultation in online databases, books, scientific articles and national and international publications, international articles indexed. The execution of this work was carried out with the three stages that characterize the Descriptive Review: the first stage consisted of the bibliographic survey in the databases; second stage consisted of reading the titles and abstracts of previously selected articles. The third stage was selected by the articles used for this study. The Internet was developed in the United States on October 29, 1969 as a result of the Cold War. The Brazilian legislation for cybercrime consists only of Law 9.609/98 entitled Software Law; Law 12.737/2012 known as Carolina Dickmann Law and Law 12.965/2014 known as the Internet Civil Framework Law. The best known cybercrimes are: Crime against honor, cyberbulling, child pornography, copyright infringement, fakeprofiles, rape crime, threat, racism and fake news. The biopsychosocial changes that affect victims of cybercrime can be physical as; tiredness, sleep disorders, enuresis, migraine, digestive disorders, nausea, body ado. Psychological disorders are fear, anger, anxiety, stress, feeling of humiliation and impotence, sadness, depression, suicidal ideation and panic syndrome.